PERAN PEMENUHAN NAFKAH KELUARGA: STUDI PEMIKIRAN ULAMA HUKUM ISLAM - Muhammad Maghfurrohman; Nonik Fajariani; Lalu Supriadi Bin Mujib (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
Supporting family success requires several components, including the economy. Good family economic conditions can often create a sakinah, mawaddah and warahmah family. In fulfilling the family economy, from an Islamic perspective, the husband is the one who is most responsible for providing for the family. However, now, especially in Indonesia, many wives or mothers also contribute to earning a living outside the home. Based on this reality, this research seeks to retrace Islamic literature related to the thoughts or interpretations of Islamic scholars/legal figures regarding the obligation to fulfill a living in the family. Is it only the husband who has the absolute right to provide maintenance or not. This research is included in library research and uses descriptive qualitative research methods. As for the research conclusions produced, in general Islamic law figures (fiqh) view that the obligation to provide for the family is the husband's responsibility. However, some fiqh scholars also hold the view that a wife is allowed to leave when the husband's condition is taken into consideration. If the husband cannot fully carry out the responsibility of earning a living in order to meet the family's needs, in that condition the wife can take on the role. Some scholars also set certain limits regarding the activities of wives who leave the house to earn a living, namely as long as they do not cause harm.